The health concepts included in the books of Islamic education for the ninth and tenth grades in Jordan - Al- burdini, Somaya Mohammad (Journal of Educational and Psychological Sciences, 2019)
The study aimed to reveal the degree of inclusion of Health Concepts in Islamic Education Books in Jordan, Through the analysis of the content of those books in order to answer the questions of the study, The study used the descriptive approach, and represented the tool to build a list of health concepts, which included twenty- one concepts , The results of the study revealed the availability of health concepts to varying degrees in the books of Islamic education (ninth and tenth) in Jordan The concepts of (non- communicable diseases, methods of prevention of disease, sources of pollution of the environment) came at a high rate, and the concepts (avoid harmful drinks and foods, misconducts, ablution, body hygiene, exercise, definition of diseases, pathogens, moderation using water and investment , Environmental damage), while the other health concepts in these books were low, such as: (personal care, health education, food balance, disease transmission methods, plant care, human role towards environmental conservation). Concepts like (Health and Sleep, Food Contamination)where absent. The results showed that the book of Islamic Education for the tenth grade was ranked first in the total repetitions (120), As the share of the book of the tenth row (65) repeatedly, and came after the book the ninth grade basic, as reached (55) repeatedly The study recommended further studies to identify health concepts in books and other stages of study.